Analysis and Comparison of Harmonic Losses of Asynchronous Traction Motor under Different Modulation Strategy - Di SHEN; Weimin CHEN; Minglei ZHOU; Chenchen WANG (机车电传动)
In the traction drive system of rail transit, the output voltage of inverters contains many low-order harmonic components. Low-order harmonic has a negative impact on the temperature rise and loss of traction motor. For this reason, the influence of different modulation modes on the harmonic loss of traction motor under low switching frequency was theoretically analyzed and compared. The influence factors of harmonic iron loss and copper loss were analyzed, and the harmonic loss models based on harmonic voltage amplitude were established respectively. By calculating the curve of harmonic voltage amplitude versus modulation ratio under three different modulation modes widely used at present, and taking the traction motor parameters of a practical EMUs as an example, the variation law of motor harmonic loss under different modulation modes was analyzed and compared. The research results could be used for reference in the selection of modulation strategies for high-power traction inverters to improve the efficiency of motor operation.